Interpersonal Coordination: Methods, Achievements, and Challenges - Cornejo, Carlos; Cuadros, Zamara; Morales, Ricardo; Paredes, Javiera (Frontiers in Psychology, 2017)
Research on interpersonal coordination can be traced back to the early 1960s, when video recording began to be used in communication studies. Since then, technological advances have extended the range of techniques that can be used to accurately study interactional phenomena. Although such a diversity of methods contributes to the improvement of knowledge on interpersonal coordination, it has become increasingly difficult to maintain a comprehensive view of the field. In the present article, we review the main capture methods, describing their major findings, levels of description and limitations. We group them into three categories: video analysis, motion tracking, and psychophysiological and neurophysiological techniques. The revised evidence suggests that interpersonal coordination encompasses a family of morphological and temporal synchronies at different levels and that it is tightly related to the construction and maintenance of a common social and affective space. We conclude by arguing that future research should address methodological challenges to advance the understanding of coordination phenomena.